Decoding the trinity of Fintech, digitalization and financial services: An integrated bibliometric analysis and thematic literature review approach - Amola Bhatt; Mayank Joshipura; Nehal Joshipura (Cogent Economics & Finance)
Technology has reshaped how financial services are designed, delivered, and consumed over the past decade. The increased mobile and internet penetration and availability of cheap data combined with the advent of Fintech, digitalization, blockchain technology, machine learning, and artificial intelligence have fast-tracked the digital transformation of economies worldwide. Covid19-induced lockdowns accelerated the digitalization of financial services. This study identifies the main areas and current dynamics of Fintech, digitalization, and financial services and suggests future research directions. Using a bibliometric analysis followed by a thematic literature review, the study examines a sample of 583 journal articles from the Scopus database from 1984 to 2021. Based on the bibliometric analysis, we identified four dominant themes. These themes are further explored through a thematic literature review to gain further insights. We conclude by suggesting potential directions for future research in the field.